A guide to the Project Management Body of Knowledge (PMBOK guide), fifth edition - Project Management Institute (Project Management Institute, 2015)
Organizational influences and project life cycle -- Project management processes -- Project integration management -- Project scope management -- Project time management -- Project cost management -- Project quality management -- Project human resource management -- Project communications management -- Project risk management -- Project procurement management -- Project stakeholder management.